Students’ Perceptions of Chatgpt Use in Vocational and Engineering Education Practicum: A Descriptive Qualitative Study - Fitrika Kumala Dewi; Ambiyar Ambiyar; M Giatman; Nurhasan Syah; Fahmi Rizal; Reni kurnia (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
The study is aimed at exploring students’ perception of using ChatGPT in the Multimedia and Internet practicum in vocational and engineering education context. The subjects of this study were 28 students of the Multimedia and Internet practicum course in Electronic Engineering Education Study Program of Universitas Negeri Padang. Data were collected through written open-ended responses and analyzed using thematic analysis using MAXQDA. The findings indicate that students viewed ChatGPT as a beneficial and practical learning aid that assisted them in searching for information, generating ideas, clarifying concepts, solving problems, and completing projects. However, students also identified a number of limitations i.e., limited responses, premium access, less accurate answers, confusing explanations and potential dependence on ChatGPT. The word-cloud analysis confirmed the thematic findings, showing dominant terms related to usefulness, ease, speed, project work, multimedia production, limitation, cost, and dependence. These results indicate that the potential of using the ChatGPT in project-based multimedia practicum needs to be accompanied by critical verification, lecturer guidance and integration with other learning resources such as modules, tutorials and hands-on practice.